(untitled) (Research, Society and Development, 2020)
Objective: to identify the main nursing care in the prevention of central venous catheter related. Methodology: This is an integrative literature review in which the descriptors were used: changes related to catheters, central venous catheters, nursing care and disease prevention. Data collection was performed in the MEDLINE, SCIELO and BDENF databases and for the definition of inclusion criteria, the time frame from 2017 to 2020 was selected, complete articles, available free of charge and in Portuguese. Articles that did not correspond to the research focus and did not contribute to a discussion and achievement of the investigated objective were excluded. Results and Discussion: The final sample consisted of 09 articles which, after analyzing its contents, identified that the main nursing care for the prevention of infection related to the central venous catheter consisted of proper hand hygiene, ostium dressings of CVC with sterile occlusive dressing, daily delivery of the catheter insertion site, equipment changes and disinfection of connectors before being accessed. Conclusion: In view of this, it is believed that the study will provide relevant information for the nursing team, as well as for the entire multidisciplinary team that provides assistance to patients with these types of invasive devices. It is also important to emphasize and the importance of developing more studies involving the topic in question, considering the context of patient safety, which should be the main objective of the entire health team.